2007
DOI: 10.1086/513429
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy and Virologic Suppression among HIV-Infected Persons Receiving Care in Private Clinics in Mumbai, India

Abstract: Self-reported adherence to ART in a sample of patients attending Mumbai's private clinics was relatively high. However, the fact that a detectable viral level was found in nearly 40% of patients suggests that second-line ART regimens, as well as an emphasis on adherence and appropriate ART regimens in India, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 37 publications
8
109
5
Order By: Relevance
“…The adjusted PAF for alcohol use was 11.4% (95% CI: 0.05-0.17), for low/intermediate general health perceptions was 37.3% (95% CI: 0.02-0.60), for high/intermediate distress was 24.0% (95% CI: À0.05-0.45), and for CD4 cell count greater than 500 cells per microliter was 10.0% (95% CI: À0.01-0.20).…”
Section: Multivariable Analysis Of Risk Factors Of Antiretroviral Nonmentioning
confidence: 98%
See 2 more Smart Citations
“…The adjusted PAF for alcohol use was 11.4% (95% CI: 0.05-0.17), for low/intermediate general health perceptions was 37.3% (95% CI: 0.02-0.60), for high/intermediate distress was 24.0% (95% CI: À0.05-0.45), and for CD4 cell count greater than 500 cells per microliter was 10.0% (95% CI: À0.01-0.20).…”
Section: Multivariable Analysis Of Risk Factors Of Antiretroviral Nonmentioning
confidence: 98%
“…15 A recent study from western India conducted at private health clinics found that among patients paying for treatment out-ofpocket, three fourths of patients had 95% adherence or higher. 24 Earlier studies monitoring treatment adherence from resource-limited setting have generally been conducted soon after patients initiated HAART, when patients were experiencing dramatic increases in health status. However, in the current study, half the population had been HAARTexperienced for over 2 years, suggesting the need for sustained efforts to maintain high levels of adherence well after the initial immune-restorative effects of treatment.…”
Section: Venkatesh Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…As per data in March 2013, there are 18.13 lakh people living with HIV/AIDS in India with around 1.16 lakh new HIV infections among adults every year. 1 As per NACO 2013 guidelines, all HIV infected patients with a CD 4 + count of ≤350 cells/mm 3 or those with WHO clinical stage 3 or 4 irrespective of CD 4 + count should be initiated on ART. 1 The regimen selected is based on their efficacy, side effects, drug availability, cost, potential drug interactions, comorbidities, opportunistic infections (OIs), and need for laboratory monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Some studies have assessed survival, morbidity and medication adherence among Indian patients receiving ART in the private and nongovernmental sectors. [3][4][5] This study examined treatment outcomes in terms of immunological improvement, improvement in weight and haemoglobin, occurrence of opportunistic infections and adverse reactions using routinely collected ART data from the tertiary care hospital setting. Further, a nonrandomized comparison study of TDF with other commonly used nucleoside reverse transcriptase inhibitors based regimens was undertaken.…”
Section: Introductionmentioning
confidence: 99%